Global warming intensifies the interference competition by a poleward-expanding invader on a native dragonfly species - Koki Nagano; Masayoshi K. Hiraiwa; Naoto Ishiwaka; Yugo Seko; Koya Hashimoto; Taizo Uchida; Francisco Sánchez-Bayo; Daisuke Hayasaka (Royal Society Open Science, 2023)
Rapid climate warming has boosted biological invasions and the distribution or expansion polewards of many species: this can cause serious impacts on local ecosystems within the invaded areas. Subsequently, native species may be exposed to threats of both interspecific competition with invaders and temperature rises. However, effects of warming on interspecific interactions, especially competition between invader and native species remains unclear. To better understand the combined threats of biological invasions and warming, the effect of temperature on competitive interactions between two dragonfly species, the expanding Trithemis aurora from Southeast Asia and the Japanese native Orthetrum albistylum speciosum were assessed based on their foraging capacity. Although the stand-alone effect of temperature on foraging intake of the native dragonfly was not apparent, its intake significantly decreased with increasing temperatures when the invader T. aurora was present. Such reductions in foraging might lead to displacement of the native species through competition for food resources. This suggests that impacts of invader species against native species are expected to be more severe when interspecific competition is exacerbated by temperature rises.